Veterinary Telemedicine: A literature review - Massin Teller, Lori; Moberly, Heather K (Veterinary Evidence, 2020)
As telemedicine becomes more mainstream in the veterinary profession, it is important to understand when and how to utilise it successfully, and its potential downsides. This literature review supports the use of veterinary telemedicine for teleconsultations, and using wearable and mobile health (mHealth) devices for monitoring animal health. Data supporting the provision of virtual care directly to a client within an established veterinarian-client-patient relationship (VCPR) is more limited, and some of what we know comes from paediatric medicine on the human side. As we have learned from human health care providers, we must be aware there could be a tendency to overprescribe antimicrobials in a virtual visit compared to an in-person visit. Data have also shown telemedicine can be just as effective in diagnosing respiratory disease when compared to traditional visits to a doctor’s office or hospital. Telemedicine is especially effective in areas where access to care is limited, whether because of geography, finances, or lack of resources. Overall, veterinary telemedicine and telehealth can provide positive results.